2008
DOI: 10.1016/j.mser.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-based biopolymers in biomedicine and biotechnology

Abstract: Peptides are emerging as a new class of biomaterials due to their unique chemical, physical, and biological properties. The development of peptide-based biomaterials is driven by the convergence of protein engineering and macromolecular self-assembly. This review covers the basic principles, applications, and prospects of peptide-based biomaterials. We focus on both chemically synthesized and genetically encoded peptides, including poly-amino acids, elastin-like polypeptides, silk-like polymers and other biopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
231
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(250 citation statements)
references
References 364 publications
2
231
0
3
Order By: Relevance
“…Herein, we review their different applications as drug/gene delivery carriers and imaging agents. Polypeptide applications cover many other areas such as their use in implants, nanogels or coatings, which are out of the scope of this review [27,30,85]. …”
Section: Polypeptides As Polymer Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we review their different applications as drug/gene delivery carriers and imaging agents. Polypeptide applications cover many other areas such as their use in implants, nanogels or coatings, which are out of the scope of this review [27,30,85]. …”
Section: Polypeptides As Polymer Therapeuticsmentioning
confidence: 99%
“…For instance, poly(glutamic acid) (PGA), poly(lysine) (PLL) or poly(aspartate) have emerged as perfect candidates as they present the required carrier features, namely, biodegradability, high drug loading capacity and well-defined structures. These polymers have been catalogued as a novel family of materials due to their physical, chemical and biological properties derived from their controlled sequences and composition [26][27][28][29][30]. Polypeptides are able to adopt stable conformations and undergo hierarchical assembles to form highly organised supramolecular structures at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Kaufmann & Weberskirch (2006) have described efficient synthetic methods for ELPs based on the solid-phase peptide synthesis using resin as solid support in the presence of HoBt/PyBob as activating agents. Chow et al (2008) have reviewed the various available methods for the synthesis of ELPs. They reported that ELPs can be synthesized via chemical methods, namely solid phase peptide synthesis as synthetic polypeptides and by recombinant DNA methodologies as genetically encoded polypeptides.…”
Section: Synthesis Of Elpsmentioning
confidence: 99%
“…This synthetic technique is, however, a cumbersome and expensive process (Chow et al, 2008). The presence of reactive side chain in these ELPs also makes them unstable over long periods of time and at higher temperatures (Nicolini et al, 2004).…”
Section: Anticancer Drug Targeting Applications Of Elpsmentioning
confidence: 99%
“…Thus, protein based scaffolds would be highly beneficial to guide spatially-and temporally-complex multicellular processes of tissue regeneration. Peptide and protein based biomaterials have emerged as a new class of biomaterials that possesses unique and often superior properties when compared to conventional materials and are widely used for regenerative and reparative medicine (2,(12)(13)(14) . The main application of peptide-based biopolymers for tissue engineering is an injectable scaffold.…”
Section: Introductionmentioning
confidence: 99%